Social capital and its role to improve maternal and child health services in Northwest Ethiopia: A qualitative study - Mengesha, E.W.; Tessema, Gizachew; Assefa, Y.; Alene, G.D. (2023)
Background: Social capital is a set of shared values that allows individuals or groups receive emotional, instrumental or financial resources flow. In Ethiopia, despite people commonly involved in social networks, there is a dearth of evidence exploring whether membership in these networks enhances uptake of maternal and child health (MCH) services. This study aimed to explore perspectives of women, religious leaders and community health workers (CHWs) on social capital to improve uptake of MCH services in Northwest Ethiopia.